Impact of a packing medium with alga Bifurcaria bifurcata extract on canned Atlantic mackerel (Scomber scombrus) quality. (20th February 2018) - Barbosa, Roberta G; Trigo, Marcos; Fett, Roseane; Aubourg, Santiago P
Abstract: BACKGROUND: The present research focused on the quality of canned fish. Its primary objective was the quality enhancement of canned Atlantic mackerel ( Scomber scombrus ) by including an aqueous Bifurcaria bifurcata extract in the packing medium. Various alga extract concentrations were tested and compared with a control without alga extract. After 3 months of canned storage, the cans were opened and quality changes in fish white muscle were analyzed. RESULTS: An inhibitory effect on lipid oxidation development (tertiary compound formation) and color parameter ( L * and b *) values was observed as a result of the alga presence in the packing medium. On the contrary, the presence of the alga extract did not produce any effect on volatile compound (total and trimethylamine) formation and lipid hydrolysis (free fatty acid formation) development. CONCLUSION: A preservative effect derived from the use of an aqueous B. bifurcata extract as packing medium is concluded, and this result is primarily linked to the presence of hydrophilic preservative molecules. The packing system proposed in this work constitutes a novel and promising strategy to enhance the quality of commercial canned fish products. © 2018 Society of Chemical Industry